Charting the Badlands: Mapping Ancient Shorelines - Schneckloth, Sara (BBDS - Black Book: Drawing and Sketching, 2024)
Charting the Badlands is an ongoing drawing project inspired by geomorphological processes and the geological legacy of the American Southwest. Drawing offers an embodied way to consider deep time on an intimate scale, compressing past, present and future. In this practice, drawing sites the land as a primary source of both inspiration and raw marking material. A handful of soil I gather while walking is transformed into pigment, purposed to map a memory of the place, a fragment of lived time, an imagined geological past or future.